The relationship between tobacco and non-alcoholic fatty liver disease incidence: a systematic review and meta-analysis of observational studies - Jin, Jianxiang; Zhang, Yuping; Huang, Yiping (Frontiers in Medicine, 2025)
BackgroundThis meta-analysis investigates the relationship between smoking and non-alcoholic fatty liver disease (NAFLD) risk.MethodsObservational studies (cohort, case-control, cross-sectional) were systematically searched in PubMed, Web of Science, EBSCO, and Cochrane Library up to December 2024. Adjusted odds ratio (OR) and corresponding 95% confidence interval (95% CI) were used to assess the association.ResultsA total of 19 studies, composing 450,130 participants were included. Active smoking significantly increased NAFLD risk (OR = 1.30, 95% CI: 1.21–1.40, p < 0.001), with stronger effects observed in current smokers (OR = 1.41, 95% CI: 1.22–1.63, p < 0.001). A dose-response relationship was evident: ≥20 pack-years of smoking elevated risk by 32% (OR = 1.32, 95% CI: 1.18–1.49, p < 0.001). Subgroup analyses revealed amplified risks in metabolically compromised individuals, including those with BMI ≥ 24 (OR = 1.43, p < 0.001), TG ≥ 1.2 mmol/L (OR = 1.41, p = 0.003), and SBP ≥ 125 mmHg (OR = 1.65, p < 0.001). Passive smoking showed a marginal association (OR = 1.13, 95% CI: 1.09–1.16, p < 0.001).ConclusionSmoking is an independent risk factor for NAFLD, particularly in individuals with metabolic dysregulation. Public health strategies targeting smoking cessation and metabolic control may mitigate NAFLD burden.Systematic review registrationhttps://www.crd.york.ac.uk/prospero/#loginpage, identifier CRD42024545970